The Influence of Humanitarian Da'wah on Community Social Piety in The Peneleh Mosque area in Surabaya - A. Fikri Amiruddin Ihsani; Md. Mosaddek Billah; St. Nur Alfiana Wulandari (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study discusses the influence of human preaching on social piety in the Peneleh Mosque area of Surabaya. The purpose of this study is to describe, explain, and find out whether there is an influence of human preaching at the Peneleh Mosque Surabaya on social piety and describe, explain, and find out how much influence the preaching of humanity in the Peneleh Mosque area of Surabaya has social piety. This study uses a quantitative research method with a survey approach. The data collection technique used was through a questionnaire distributed to the sample. The collected data is then analyzed, compared, and combined to form a systematic, coherent, and measurable study result. In this study, it was found that; (1) There is a relationship between the influence of preaching humanity on social piety in the Peneleh Mosque area of Surabaya. (2) The influence of preaching humanity on social piety in the environment of the Peneleh Mosque area of Surabaya is moderate. Thus, it can be concluded that this study shows the working hypothesis (H1) is successful. That is, there is an influence between the preaching of humanity on social piety in the Peneleh Mosque area of Surabaya.